Hablando del patrimonio cultural: historia oral escolar y fuentes orales en la enseñanza patrimonial (2014)
Patrimonial education confronts teachers to various challenges due to the quick disappearance ofmany past scenarios in today´s cities and the responsibility of generating patrimonial consciousness ina world described by Pierre Nora as ¨Prey of immediacy¨ This circumstance requires finding effectivemethodological strategies to teach the contents of Civic Education, Social Sciences and History. To thisrespect, School Oral History and oral sources offer various alternatives and the following work exploressome of them.